2022
DOI: 10.3390/ma15196799
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Friction Stir Deposition Technique to Refill Keyhole of Friction Stir Spot Welded AA6082-T6 Dissimilar Joints of Different Sheet Thicknesses

Abstract: Joining dissimilar sheet thicknesses of AA6082-T6 alloys by friction stir spot welding (FSSW) provides many advantages in automotive and aerospace applications. The formed keyhole at the end of the FSSW process is one of the typical features after the welding process, which owns the same size as the rotating pin that remains at the joint center. This keyhole destroys the joint continuity and can stimulate serious stress concentration when the FSSW joint bears an external force. To solve this issue, a novel ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Increasing TS from 100 to 300 mm/min generally increases the hardness values for the applied pin geometries. This hardness trend is probably due to decreased PZ temperature (heat input) with increasing TS [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing TS from 100 to 300 mm/min generally increases the hardness values for the applied pin geometries. This hardness trend is probably due to decreased PZ temperature (heat input) with increasing TS [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the refilling technique enhances the spot joint quality and strength. Recently, Ahmed et al [86] developed a refill technique based on friction stir deposition [87][88][89][90][91][92]. They reported that the RFSSW lap joints of AA6082 that were filled with AA2011 showed higher tensile shear loads than those of the FSSW (before refill) lap joints.…”
Section: Friction Stir Spot Weldingmentioning
confidence: 99%
“…They reported that the RFSSW lap joints of AA6082 that were filled with AA2011 showed higher tensile shear loads than those of the FSSW (before refill) lap joints. The RFSSW joint (welded at 600 rpm/3 s and refilled at 400 rpm/1 mm/min) showed a higher tensile shear load of 5400 N ± 100 compared with that recorded by the unfilled joint (4300 N ± 80) [86]. Zu et al [93,94] investigated the RFSSW of 2.0 mm-thick 2219-O (upper plate) and 2219-C10S (lower plate) with a different thickness.…”
Section: Friction Stir Spot Weldingmentioning
confidence: 99%
“…The refill friction stir spot welding (RFSSW) method is essentially a solid-phase welding technique in which the welding temperature is lower than the melting point of the material [1,2]. Due to its significant advantages of a small heat-affected zone and microstructure deformation, as well as small welding deformation, it has better application prospects in the fields of aerospace, automotive manufacturing, shipbuilding, and other industries [3][4][5].…”
Section: Introductionmentioning
confidence: 99%